Engineering a Human Pluripotent Stem Cell-Based in vitro Microphysiological System for Studying the Metformin Response in Aortic Smooth Muscle Cells - Chen, Nan; Abudupataer, Mieradilijiang; Feng, Sisi; Zhu, Shichao; Ma, Wenrui; Li, Jun; Lai, Hao; Zhu, Kai; Wang, Chunsheng (Frontiers in Bioengineering and Biotechnology, 2021)
Aortic aneurysm is a common cardiovascular disease characterized by continuous dilation of aorta and puts heavy burden on worldwide healthcare. Few drugs have been proved to be effective on controlling the progression of aortic aneurysm. The preclinical drug responses from traditional cell culture and animals are usually controversial. The effective in vitro model is of great demand for successful drug screening. Herein, we induced an in vitro micro-physiological system to test metformin, which is a potential drug for treatment of aortic aneurysm. A human pluripotent stem cells-derived aortic smooth muscle cells (hPSC-HASMCs) were cultured on an in vitro micro-physiological system, which could replicate the cyclic stretch of human native aortic wall. By using this system, we found HASMCs were more likely to present a physiologically contractile phenotype than static cell culture. Moreover, we used the hPSC-HASMCs in our micro-physiological system to perform the drug screening of metformin. The results showed that hPSC-HASMCs presented more contractile phenotype via the NOTCH 1 signaling while being treated with metformin. It indicated that metformin could be potentially used to rescue HASMCs from phenotype switching during aortic aneurysm progression. This study provides insights into the potential drug target for treatment of aortic aneurysm.